Right to Sanitation: Case Study of Indonesia - Devi Triasari (Journal of Human Rights, Culture and Legal System, 2021)
Sanitation is a basic human right which shows that someone is dignified and deserves to be respected as a human being. The international community has recognized the importance of this right. However, this right has not been explicitly recognized. This is because the legal status of the right to sanitation is unclear. The right to sanitation is derived from the "right to health" and "right to a decent standard of living". The results concluded that the fact that Indonesia is the 4th country with the largest population in the world puts Indonesia in the top 10 of the category of "country with the longest queue order of toilets" and "the country with the number of defecating in open area". International law which is often criticized for its weak enforcement in reality has been able to respond to the issue of the right to sanitation in Indonesia, mainly through 3 main mechanisms, namely reporting, country missions, and cooperation with civil Societies and NGOS. However, there are still some challenges from the three international human rights law capacities. By improving this capacity, his expectation of Goal 6 on sanitation rights can be realized by 2030.